Comparison studies of machinability for aluminium, mild steel and heat treated mild steel - Faiz Asyraf, Roslan (2008)
In recent years, industry spend almost quarter amount of the actual annual spend only for performing the metal removal operation. In order to cut this amount, it is necessary to understand the machining process that shall be done and the machinability of the material. While machining is the process designed to change the size, shape, and surface of a material through removal of materials, machinability came as important as the ease with which it can be machined. However, machinability is not a property of a material but an attribute. With this attribute, there are four major factors which are surface roughness, chip formation, tool life and cutting force. Material made of aluminum and mild steel is widely use since they are the cheapest material compare to the other steel that not require very high strength. Therefore, to manufacture components economically, engineers are challenged to find ways to improve machinability without harming performance. Machinability can be difficult to predict because machining is such a complex process. In short, a good material with good machinability is the one that require low power consumption, low tool life and have high surface finish rate without surface damage.